Meningkatkan Kualitas Pembelajaran Melalui Media Interaktif Berbasis Multimedia - Chandra Ramadhan; Mamok Andri Senubekti; Nurdiansyah Nurdiansyah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
The development of technology has brought significant changes in the world of education, one of which is through the use of multimedia as a learning tool. Multimedia, which includes text, images, audio, video, and animation, is able to increase the effectiveness of the teaching and learning process by presenting material in a more interactive and interesting way. This journal discusses various aspects of multimedia utilization in education, ranging from the types of multimedia, the benefits obtained, to the challenges in its application. Using the literature study method, this journal highlights the importance of multimedia integration in modern learning to create a more effective and innovative learning experience.